An axiomatic/asymptotic evaluation of the best theories for free vibration of laminated and sandwich shells using non-polynomial functions. (1st October 2018) - Monge, J.C.; Mantari, J.L.; Charca, S.; Vladimir, N.
Highlights: Shell theories have been constructed using Axiomatic/Asymptotic Method (AAM). The refined models are implemented following the compactness of a unified formulation. Best theory diagrams (BTDs) for free vibration of laminated and sandwich shell. BTDs are built from non-polynomial functions. BTDs with non-polynomial terms can improve the performance of deformation theories. Abstract: This paper presents Best Theory Diagrams (BTDs) constructed from non-polynomial terms to identify best shell theories for the free vibration analysis of laminated and sandwich shell. The shell theories have been constructed using Axiomatic/Asymptotic Method (AAM). The refined models are implemented following the compactness of a unified formulation developed. The governing equations are derived from the Hamilton's Principle. Navier-Type solution technique is used for solving the eigenvalue problem of simply supported shell. The BTDs use 3D equilibrium solutions as a reference. The BTDs built from non-polynomial functions are compared with Maclaurin expansions. The results are compared with Layerwise solutions. Cylindrical and spherical shells with different layer-configurations are investigated. The results demonstrate that the shell models obtained from the BTD using non-polynomial terms can improve the accuracy obtained from Maclaurin expansion for a given order of expansion of a displacement field.